The Size Fractionation and Speciation of Iron in the Longqi Hydrothermal Plumes on the Southwest Indian Ridge. Issue 6 (21st June 2019) - Wang, Hu; Yan, Qiaoyang; Yang, Qunhui; Ji, Fuwu; Wong, Kuo Hong; Zhou, Huaiyang
Abstract: The distribution and composition of Fe in hydrothermal plumes are crucial for understanding the contribution of hydrothermal venting to the oceanic Fe inventory. In this study, we conduct the first complete investigation of the size fractions of Fe and Fe‐binding ligands in the Longqi hydrothermal plumes on the Southwest Indian Ridge, combining the approaches of the size partitioning and reverse titration‐competitive ligand exchange‐adsorptive cathodic stripping voltammetry. Concentrations of all the Fe fractions were very high in the plume samples, and dissolved Fe (<0.2 μm) constituted a significant portion (48.7 ± 7.9%) of total Fe, which might be related to the existence of colloidal Fe oxyhydroxides and sulfides, as well as organic Fe complexes. Dissolved Fe consisted of colloidal Fe (10 kDa to 0.2 μm, 70.2%) and soluble Fe (<10 kDa, 29.8%). Colloidal Fe mainly contained Fe oxyhydroxides and sulfides (86.4 ± 6.2%), while most of the soluble Fe were organic Fe complexes (65.7 ± 5.4%). Fe speciation analyses showed that dissolved ligand concentrations were high in the hydrothermal plumes but were significantly lower than the dissolved Fe concentrations. Inferring from previous studies in the Longqi hydrothermal field, the ligands were most likely derived from the diffuse flow adjacent to the hydrothermal vents. The conditional stability constants (logK′FeL ) of dissolved FeL (20.4 ± 0.5) were slightly higher than those of soluble FeL (19.6 ± 0.4), although they were not statistically different. Based on the ligands' size partitioning, the soluble ligands stabilized 8.8 ± 3.8% of the hydrothermal Fe, which is over 2 times that of the colloidal ligands, 4.0 ± 1.8%. Key Points: The physical partitioning and chemical compositions of Fe in the same hydrothermal plumes over the Southwest Indian Ridge are presented Colloidal Fe constitutes most of the dissolved Fe, and the compositions of colloidal and soluble Fe in hydrothermal plumes are different The soluble ligand‐stabilized hydrothermal Fe is more than 2 times higher than that of colloidal ligands